2016
DOI: 10.1371/journal.pone.0163439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotypes and Comorbidity in European Sleep Apnoea Patients

Abstract: BackgroundClinical presentation phenotypes of obstructive sleep apnoea (OSA) and their association with comorbidity as well as impact on adherence to continuous positive airway pressure (CPAP) treatment have not been established.MethodsA prospective follow-up cohort of adult patients with OSA (apnoea-hypopnoea index (AHI) of ≥5/h) from 17 European countries and Israel (n = 6,555) was divided into four clinical presentation phenotypes based on daytime symptoms labelled as excessive daytime sleepiness (“EDS”) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 41 publications
10
110
2
2
Order By: Relevance
“…The European Sleep Apnea Database (ESADA) study analysed similar OSA phenotypes, i.e. a combination of diurnal and nocturnal symptoms, in a multicentre large cohort [89]. Results were similar to those of YE et al [87] and coworkers, with an additional finding of a high prevalence of psychiatric comorbidities, especially in OSA patients reporting symptoms of insomnia.…”
Section: Clinical Phenotypes Of Osasupporting
confidence: 74%
See 1 more Smart Citation
“…The European Sleep Apnea Database (ESADA) study analysed similar OSA phenotypes, i.e. a combination of diurnal and nocturnal symptoms, in a multicentre large cohort [89]. Results were similar to those of YE et al [87] and coworkers, with an additional finding of a high prevalence of psychiatric comorbidities, especially in OSA patients reporting symptoms of insomnia.…”
Section: Clinical Phenotypes Of Osasupporting
confidence: 74%
“…Variability in results can be expected, since the studies differed in the variables entered in the analyses. In addition, the studies are heterogeneous in the number of patients included, and only three studies were multicentric [89,90,93]. Finally, the complexity of OSA can affect the results.…”
Section: Clinical Phenotypes Of Osamentioning
confidence: 99%
“…For example, OSA has historically been conceptualized as a disorder impacting middle-aged and older-adult males, who are overweight or obese and present with complaints of excessive daytime sleepiness, tiredness, sedation, and snoring. Although epidemiological studies provide statistical support for these 'risk factors' (e.g., OSA is associated with male gender, increased age, overweight and obesity, snoring, and daytime sleepiness [14]), reliance on this single profile clearly does not represent all OSA sufferers [26][27][28]. Alternatively, insomnia has historically been conceptualized as a disorder primarily impacting middle-aged and older-adult females who are predisposed to anxiety, stress, and cycles of cognitive rumination.…”
Section: The Beginning Of Comisa Researchmentioning
confidence: 99%
“…[40]. Between 2013 and 2018, a number of large cluster analyses of OSA samples also identified that 32%-54% of OSA patients indicate symptoms of 'disturbed sleep', characterized by nocturnal insomnia symptoms, more frequent use of sedative-hypnotic medications, and lower use of CPAP therapy [26,27,41,42]. Most recently, Zhang and colleagues conducted a systematic review and meta-analysis including 37 studies investigating the co-morbidity of insomnia and OSA, and reported that 35% of insomnia patients have an AHI of ≥5, and 29% have an AHI of ≥15, while 38% of OSA patients meet insomnia criteria [43].…”
Section: Comisa Prevalencementioning
confidence: 99%
“…Over the last several decades, we have witnessed substantial increases in the granularity of the morbid phenotype of OSA, and such observations have prompted us to rethink some of the stricter early concepts. Among them, rather than viewing OSA as a single disease model that is applicable to all patients, we have formulated the conceptual framework of distinct phenotypes of OSA that may be driven by different mechanisms, link to different clinical manifestations, and display divergent responses to therapy [1][2][3][4][5][6]. In this contextual setting, the aspirational goals of the field are to first and foremost identify those OSA patients likely to benefit from treatment and administer the correct intervention, i.e.…”
mentioning
confidence: 99%